Review on Passive, Active, and Hybrid Adaptive-Morphing Flapping Wing for Energy Efficient Bird Sized UAV - Guo, Jiaqing; Abdullah, Ermira Junita; Abdul Hamid, Mohd Faisal (Progress in Aerospace and Aviation Technology, 2025)
Unmanned aerial vehicles (UAVs) with flapping wings are a promising bio-inspired technology that offers special benefits like increased agility, energy efficiency, and adaptability for both natural and urban settings.  Recent developments in flapping wing UAV development are examined in this review, with particular attention paid to material innovations, aerodynamic optimization, and passive and active morphing mechanisms.  Quantitative evidence across multiple studies indicates that passive morphing such as elastic joints and borehole designs can reduce power consumption by 10–27% and enhance lift generation by 16–40%, while active morphing enabled by actuators and smart materials improves maneuverability, stability, and load adaptability in dynamic flight conditions. Aerodynamic interactions have been better understood thanks to computational tools like Computational Fluid Dynamics (CFD) and experimental techniques like wind tunnel testing, which have also yielded important insights into performance optimization. Despite these advances, persistent challenges remain in computational cost, structural complexity, and sustained energy efficiency during extended missions. Unlike previous reviews that focus mainly on kinematics or control, this work uniquely integrates a cross disciplinary synthesis of morphing mechanisms, materials, and aerodynamic modeling to identify performance tradeoffs and emerging trends. Future research directions include AI-assisted control architectures, adaptive composite materials, and hybrid morphing designs that can transform flapping wing UAVs from laboratory prototypes into field ready systems for environmental monitoring, surveillance, and confined space operations.